Synthesis, Characterization and in vitro Antimicrobial Evaluation of Chalconeimine Derivatives as Potential Inhibitors against Enzymes Produced from S. aureus: A Computational Approach - Prithivirajan, B.; Sonia Jas, M. Jebastin; Marimuthu, G. (Asian Journal of Chemistry, 2019)
(Z)-1-(Benzo[d][1,3]dioxol-5-yl)-3-(4-(difluoromethoxy)-3-hydroxyphenyl)prop-2-en-1-one hydrazone derivatives pronounced in this manuscript represents a new collection of antibacterial agents in addition to the DNA gyrase inhibitors. Efforts had been made to synthesize those chalcone-hydrazone derivatives (4a-e) in good yields. The literature survey confirms that nano-ZnO as heterogeneous catalyst has obtained big interest because of its ecofriendly nature and has been explored as a effective catalyst for several organic ameliorations. Subsequently, induced by way of these observations and in continuation to our interest in organic synthesis with using nanocatalyst. in vitro Antibacterial activity has been evaluated towards Gram-positive and Gram-negative bacterial strains for all compounds. So one can discover the affinity to bacterial proteins docking have a look at have been carried out for 5 synthesized derivatives, antibiotic drug and co-crystallized ligands with special mechanism of action DNA gyrase B and methylthioadenosine/S-adenosylhomocysteine nucleosidase (MTAN) the usage of AutoDock 4.